Connecting philosophy and practice: implications of two philosophic approaches to pain for nurses' expert clinical decision making - Pesut, Barbara (Nursing philosophy, 2007)
McCaffery's definition of pain as ‘whatever the patient says it is’ was truly revolutionary for nursing because of its capacity to lend credibility to the patient's pain experience. However, this definition, still widely in use, represents a particular philosophic approach to pain that has limitations for nurses' expert clinical decision making. In this paper, we trace the evolution of explanations for pain and discuss two philosophic approaches to pain that are common today. The first approach, the externalist perceptual view of pain, considers pain as a perceptual experience, one that like any perceptual experience can be ‘misperceived’ by the person having the experience. The second approach, the non-representational view of pain, considers pain as a holistic experience, one where physical and existential aspects necessarily coincide. These two approaches, while both emphasizing the importance of believing the patient's expression, have different implications for clinical decision making. Only the first approach permits nurses to exercise the nuanced judgement that differentiates pain from other related conditions such as anxiety, suffering or meaninglessness.